Page 1 of 4
1
2
3
... LastLast
  1. #1

    i suck at math-stil funny though

    give me any number between 1 and 13
    lets call this number x

    so here goes.

    chose a random number between 1 and 13 we will call this number X.

    (x+4) multiplied by 2 -6 devided by 2 minus x

    so basicly (x+4)x2-6/2-x

    then you will know what number they are left with.

    the number 1

    lets say my number is 7

    7+4=11
    x 2 = 22
    -6 =16
    16/2 =8
    -7=1

    i found this kinda fun (you know any other non smart "tricks" we can use at a party)?)
    Last edited by bjarnespz; 2012-11-30 at 09:35 PM.

  2. #2
    The formula is wrong.

    ((7+4)*2-6)/2-7) = 1
    Last edited by MMKing; 2012-11-30 at 09:59 PM.

  3. #3
    Pandaren Monk Auloria's Avatar
    Join Date
    Nov 2010
    Location
    USA
    Posts
    1,941
    ((x+4)*2-6)/2-x)
    (((2x + 8) - 6)/2 - x)
    ((2x + 2)/2 -x)
    (x + 1 - x)
    1


    Algebra.

  4. #4
    I don't remember exactly what it was, but back in high school I used the various kinematics equations and a lot of substitution to prove that x = .5x. There was a major flaw of course, but I used so much substitution with the equations that it was impossible to follow. A little math sleight of hand so to say. Wish I could remember how I did it exactly
    Quote Originally Posted by Boubouille View Post
    Stop out of topic conversation, or I'll show you my giant hammer.

    PS: The hammer is my penis.

  5. #5
    Pandaren Monk Auloria's Avatar
    Join Date
    Nov 2010
    Location
    USA
    Posts
    1,941
    Quote Originally Posted by Arcilux View Post
    I don't remember exactly what it was, but back in high school I used the various kinematics equations and a lot of substitution to prove that x = .5x. There was a major flaw of course, but I used so much substitution with the equations that it was impossible to follow. A little math sleight of hand so to say. Wish I could remember how I did it exactly
    There are some tricks you can do with squaring numbers. If you square a negative number, you get a positive one, but most of the time people forget that when you take the square root of a number, it can be either positive or negative, so you can lead them to a false result.

  6. #6
    Field Marshal skoging's Avatar
    Join Date
    Jan 2008
    Location
    Bergen, Norway
    Posts
    81
    (((x + 4) *2 - 6) / 2) - x = (x + 4) - 3 - x = 4 - 3 = 1

    Just math basically, nothing fancy.
    Quote Originally Posted by Tulduru
    He is the hero that Azeroth deserves, but not the one it needs right now. And so we'll mock his alpha prediction. Because he can take it. Because he's not a hero. He's a silent poster, a watchful dataminer....The MMO Champion.

    Hitz From Dah Boing

  7. #7
    Herald of the Titans
    Join Date
    Apr 2010
    Location
    Vineland, Cumberland, NJ, USA
    Posts
    2,580
    1] a=b
    2] a+a=a+b
    3] 2a=a+b
    4] 2a-2b=a+b-2b
    5] 2a-2b=a-b
    6] 2(a-b)=(a-b)
    7] 2=1

    Two things:
    1) between lines 6 and 7 I skipped a simple but important notation. That cancellation here is equivalent to division by (a-b)
    the line should be 6.5] 2(a-b)/a(-b)=(a-b)/(a-b)
    2) the first line states that a=b therefore (a-b)=0 and threfore the line 6.5] is division by zero which leads to an inconsistent result.


  8. #8
    Quote Originally Posted by Linkedblade View Post
    1] a=b
    2] a+a=a+b
    3] 2a=a+b
    4] 2a-2b=a+b-2b
    5] 2a-2b=a-b
    6] 2(a-b)=(a-b)
    7] 2=1

    Two things:
    1) between lines 6 and 7 I skipped a simple but important notation. That cancellation here is equivalent to division by (a-b)
    the line should be 6.5] 2(a-b)/a(-b)=(a-b)/(a-b)
    2) the first line states that a=b therefore (a-b)=0 and threfore the line 6.5] is division by zero which leads to an inconsistent result.

    You sir, finally explained to me just how terrible division by 0 is.

  9. #9
    Quote Originally Posted by Linkedblade View Post
    1] a=b
    2] a+a=a+b
    3] 2a=a+b
    4] 2a-2b=a+b-2b
    5] 2a-2b=a-b
    6] 2(a-b)=(a-b)
    7] 2=1

    Two things:
    1) between lines 6 and 7 I skipped a simple but important notation. That cancellation here is equivalent to division by (a-b)
    the line should be 6.5] 2(a-b)/a(-b)=(a-b)/(a-b)
    2) the first line states that a=b therefore (a-b)=0 and threfore the line 6.5] is division by zero which leads to an inconsistent result.

    That's just a convoluted version of 1x0 = 0 = -1x0 :P

    The one that can actually have people confused is this:

    By definition: sqrt(-1) = i
    Note: sqrt = square root of

    So, -1 = i*i (ie square of i)
    =sqrt (-1) * sqrt (-1)
    =sqrt (-1 * -1)
    =sqrt (1)
    =1

    So, -1 = 1

  10. #10
    Quote Originally Posted by ecthrund View Post
    By definition: sqrt(-1) = i
    Note: sqrt = square root of

    So, -1 = i*i (ie square of i)
    =sqrt (-1) * sqrt (-1)
    =sqrt (-1 * -1)
    =sqrt (1)
    =1

    So, -1 = 1
    You missed out 2 vital parts of the definition.

    √-1 = ±i
    √1 = ±1

    Then your formula works.

  11. #11
    Banned sandmoth12's Avatar
    Join Date
    Aug 2011
    Location
    California
    Posts
    1,767
    I can find the sum of all the numbers 1,2,3...all the way to 1000 in under a minute.

    Simple add the first number plus the last number squared then divide by 2. Tada you have the sum of all those numbers !

    ---------- Post added 2012-12-01 at 02:22 PM ----------

    1/3=.3333...

    1=.9999...

    Voodoo magic!

  12. #12
    Quote Originally Posted by Twoddle View Post
    You missed out 2 vital parts of the definition.

    √-1 = ±i
    √1 = ±1

    Then your formula works.
    That is a pretty common misconception.

    x*x = a, this implies x = sqrt(a) or -sqrt(a)

    But the square root itself always yields a positive number; it is by definition. So, sqrt (1) = 1 and NOT -1.

    The problem with the -1 = 1 "proof" is that sqrt(-1)*sqrt(-1) DOES NOT EQUAL sqrt (-1*-1). Why? Because sqrt(a)*sqrt(b) = sqrt(ab) is true only if at least one of a and b is non-negative.

    It is relatively advanced Maths, although still school level, but I absolutely loved this one when I was back in school. Complex numbers can be complex

  13. #13
    Fluffy Kitten Kasierith's Avatar
    Join Date
    Jul 2010
    Location
    St Petersburg
    Posts
    9,878
    One of two things. First, if you have 24 people in the same room, there is a 47% chance or somewhere around there that 2 people will have the same birthday. It may sound ridiculous, but the math follows it steadily.
    '
    Second, the Collatz conjecture. Its a teeny bit wordy, and it helps to have a visual aid, so I'll reference my favorite beloved web comic.

  14. #14
    Quote Originally Posted by sandmoth12 View Post
    1/3=.3333...

    1=.9999...

    Voodoo magic!
    Its true, although it did seem fishy when I saw this the first time way back. For the uninitiated, here is how:

    Let x = 0.99999... (Eqn 1)

    10x = 9.99999... (Eqn 2)

    Subtract Eqn1 from Eqn 2:

    10x-x = (9.99999...) - (0.99999...)
    or, 9x = 9
    or, x = 1

    Voila! 0.99999... is actually equal to 1! Things like these make me want to study Maths

  15. #15
    You can do some neat things with fractions in binary too. For example 1/10 in binary is actually an infinitely repeated decimal which can make computers have some really interesting calculations. If you string together a bunch of calculations those little errors can be compounded
    Quote Originally Posted by Boubouille View Post
    Stop out of topic conversation, or I'll show you my giant hammer.

    PS: The hammer is my penis.

  16. #16
    1+1+1+1+1....= -1/2

    True stuff
    -You are now breathing manually-

  17. #17
    Herald of the Titans
    Join Date
    Apr 2010
    Location
    Vineland, Cumberland, NJ, USA
    Posts
    2,580
    Quote Originally Posted by someotherguy View Post
    You sir, finally explained to me just how terrible division by 0 is.
    Yeah, it is terrible, in fact when dealing with multiplication 0 isn't even in the group. >.>

  18. #18
    Quote Originally Posted by ecthrund View Post
    That is a pretty common misconception.

    x*x = a, this implies x = sqrt(a) or -sqrt(a)

    But the square root itself always yields a positive number; it is by definition. So, sqrt (1) = 1 and NOT -1.

    The problem with the -1 = 1 "proof" is that sqrt(-1)*sqrt(-1) DOES NOT EQUAL sqrt (-1*-1). Why? Because sqrt(a)*sqrt(b) = sqrt(ab) is true only if at least one of a and b is non-negative.

    It is relatively advanced Maths, although still school level, but I absolutely loved this one when I was back in school. Complex numbers can be complex
    I take issue with this. It's almost as if you are saying that since sqrt(4) by definition is 2, that -2*-2 doesn't equal four.

  19. #19
    Herald of the Titans
    Join Date
    Apr 2010
    Location
    Vineland, Cumberland, NJ, USA
    Posts
    2,580
    Quote Originally Posted by psionicmonkey View Post
    I take issue with this. It's almost as if you are saying that since sqrt(4) by definition is 2, that -2*-2 doesn't equal four.
    Well normally, especially intermediate schools, when you see sqrt(4) it is understood to be the positive square root of 4. And it really screws with some people seeing as when algebra comes around and you go to solve a quadratic you wind up with the positive or negative operator.

    Addedndum: Also he is correct. Normally when you have √(a)*√(b) you could assume it equals √(ab), however that is only true for REAL, NON-NEGATIVE numbers. So once you begin to mention i you have left the subset that you were working in. Reals are a subset of the Complex numbers and when working in complex numbers you have other rules to use.
    Last edited by Linkedblade; 2012-12-02 at 09:45 PM.

  20. #20
    Quote Originally Posted by psionicmonkey View Post
    I take issue with this. It's almost as if you are saying that since sqrt(4) by definition is 2, that -2*-2 doesn't equal four.
    No, what I am saying is that if x2 = 4, then x = +sqrt(4) or -sqrt(4), but the sqrt(4) itself always equals 2. It is by definition - the Square Root function is defined that way.

    I know it can mess with people's heads. It is kind of like the confusion between centripetal and centrifugal acceleation/force in Mechanics.

Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts
  •